EVALUATION OF NIGELLA SATIVA L. CALLUS EXTRACTS UNDER ELICITATION FOR PHYTOCHEMICAL AND ANTIBACTERIAL ACTIVITY - HERA CHAUDHRY,; NIDA FATIMA,; IFFAT ZAREEN AHMAD, (International Journal of Pharma and Bio Sciences, 2014)
The indiscriminate use of commercial antimicrobial drugs has resulted in multiple drug resistance and adverse effects on the host. The present study was aimed to elucidate the effect of different biotic/abiotic elicitors on the growth as well as to enhance the metabolite production in leaf and epicotyl calli of Nigella sativa. Further, antibacterial activity of these callus extracts was evaluated against five Gram positive and Gram negative bacteria. TLC data confirmed the presence of alkaloids, phenols, flavonoids, glycosides and importantly terpenoids in control and elicitated callus extracts. Calculated MIC values showed that maximum inhibition was caused by MnCl2 (1.08±0.3 µg ml-1), pectin (1.28±0.5 µg ml-1) and control epicotyl callus (2.02±0.3 µg ml-1) and minimum by CoCl2 and cellulose leaf callus where E. coli being most sensitive followed by S. typhi, B. cereus, S. aureus K. pneumoniae towards the extracts. Results showed that the extracts were better antibacterial agents when compared with commercially available antibiotics.